2021
DOI: 10.1002/mco2.104
|View full text |Cite
|
Sign up to set email alerts
|

NF‐κB signaling in inflammation and cancer

Abstract: Since nuclear factor of κ‐light chain of enhancer‐activated B cells (NF‐κB) was discovered in 1986, extraordinary efforts have been made to understand the function and regulating mechanism of NF‐κB for 35 years, which lead to significant progress. Meanwhile, the molecular mechanisms regulating NF‐κB activation have also been illuminated, the cascades of signaling events leading to NF‐κB activity and key components of the NF‐κB pathway are also identified. It has been suggested NF‐κB plays an important role in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
118
0
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(127 citation statements)
references
References 464 publications
(516 reference statements)
1
118
0
8
Order By: Relevance
“…Such positive regulation by SHP2, through dephosphorylation of TLR7 at Tyr1024, promotes the trafficking of TLR7 to the endosome and maintains excessive activation of TLR7/NF‐κB signaling, thus aggravating skin inflammation. 28 , 37 In addition, NETs’ formation is increased in both peripheral blood and lesion skin of psoriasis patients and correlates with disease severity. 38 However, whether there is a regulatory relationship between SHP2 and NETs in neutrophils and how SHP2 influences NETs to promote psoriasis remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such positive regulation by SHP2, through dephosphorylation of TLR7 at Tyr1024, promotes the trafficking of TLR7 to the endosome and maintains excessive activation of TLR7/NF‐κB signaling, thus aggravating skin inflammation. 28 , 37 In addition, NETs’ formation is increased in both peripheral blood and lesion skin of psoriasis patients and correlates with disease severity. 38 However, whether there is a regulatory relationship between SHP2 and NETs in neutrophils and how SHP2 influences NETs to promote psoriasis remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…We revealed a novel regulation by SHP2 of TLR7‐mediated NF‐κB signaling activation in macrophages. Such positive regulation by SHP2, through dephosphorylation of TLR7 at Tyr1024, promotes the trafficking of TLR7 to the endosome and maintains excessive activation of TLR7/NF‐κB signaling, thus aggravating skin inflammation 28,37 . In addition, NETs’ formation is increased in both peripheral blood and lesion skin of psoriasis patients and correlates with disease severity 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Natural extracts have been linked to therapeutic molecules that modulate oxidative stress-mediated toxicity, including acute liver failure [11]. Hepatic tissue MDA levels, SOD, and CAT activity were determined in hepatic cells to further investigate THY's protective effect.…”
Section: Thymoquinone's Effects On Dox-induced Oxidative Stress Marke...mentioning
confidence: 99%
“…Furthermore, excessive ROS production can cause inflammation by activating the transcription factor (NF-kB), resulting in the massive production of cell adhesion molecules, chemokines, and pro-inflammatory cytokines, thereby increasing DOX cytotoxicity. Research has found that the inflammation-related transcription factor NF-kB, as well as its interaction with apoptosis, can cause hepatic injury [10][11][12]. A variety of active herbal extracts or active components derived from herbal medicines have been shown in earlier studies to be highly effective at counteracting the adverse effects of DOX [13].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, NF-κB p65 (RELA) gene expression was reported to be increased in TNBC compared to that in other subtypes, deeply involved in TNBC stem cell survival, and activated during the recurrence of breast cancers, including TNBC [ 4 , 5 , 6 ]. NF-κB, a transcription factor that promotes cell proliferation, differentiation, and survival, is involved in tumorigenesis and cancer survival in various solid tumors, including pancreatic, lung, cervical, prostate, breast, and gastric cancers [ 7 ]. Therefore, NF-κB may be a new therapeutic target molecule for TNBC.…”
Section: Introductionmentioning
confidence: 99%